Sejarah dan Karakteristik Sastra Anak - Rindayanti Rindayanti; Rahma Ashari Hamzah; Fika Nurfadilah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
As discussed in this paper, children's literature plays an important role in shaping children's imagination, moral values, and language skills from an early age. Children's literature not only functions as entertainment, but also as a source of learning that can help children form positive characters and think critically. This study starts from written pre-literature to contemporary literature, showing how the form and function of children's stories change with the development of technology and the times. In addition, this paper discusses several characteristics of children's literature, such as the use of easy-to-understand language, interesting illustrations, and themes that are appropriate to the world of children. This study aims to broaden our understanding of the role of children's literature in education, especially in learning in elementary schools. With a good understanding, parents and teachers are expected to be able to choose and deliver readings that help the development of children's literacy and personality.